Push Up Exercise Against 50 Meter Swimming Speed Breaststroke - Nikmatun Nazilah; Silvi Aryanti; Ahmad Richard Victorian (UNIB Press, 2023)
The aim of this study was to evaluate the influence of push-up training on improving the speed of breaststroke swimming in athletes who are members of the Palembang Tirta Sriwijaya Aquatic Club (TSAC). This study was conducted as an experiment using a one-group pretest and posttest research design. The research subjects included athletes who are part of the Palembang Tirta Sriwijaya Aquatic Club (TSAC). The research sample involved all members of age group III with an age range of 12-13 years consisting of 30 individual athletes. The tool used to measure variables is the breaststroke swimming test using a distance of 50 meters. The data analysis was conducted utilizing the T-test. Based on the analysis results, the t-value exceeded 4.762, while the t-table value was 2.045. These results indicate a significant difference between the pretest push-up and posttest push-up groups in relation to the improvement in 50-meter breaststroke swimming speed. The conclusion of this study revealed that push-up exercises had a positive impact on increasing breaststroke swimming speed as far as 50 meters.